Integration & Impact of Information Technology on Indian Economy - Salim, Gulrukh (Journal of Commerce and Trade, 2014)
India occupies a major place in list of developing countries and is expected to have basic capabilities to compete with world economies. Before 1991, India adopted policy of self-reliance but in this era of LPG, India’s industrial and agricultural structure is being transformed into open and mixed economy. On the basis of various surveys and fact conducted by National and International Agencies, India is still lacking in the basic needs of livelihood, despite having occupied the position of third largest economy of the world. . Now the rising demand for the sustainability of Indian economy is to jump into development process, global integration and optimum use and magnitude of resources. Information technology is offering new techniques of sharing information and transacting business with the change in the nature of financial and other service sectors, providing the accurate means of using the individual and institutional worth of countries in both public and private sector. The basic emphasis of this paper is on the integration of world economy to Indian economy, considering various factors, risks and major contribution by leading organizations like BRICS, WTO etc. and the impact of Information Technology on Indian economy.